Morphologicals and molecular characteristics of regang prawn (Macrobrachium sintangense De Man, 1898) from Special Region of Yogyakarta - Rahmawati, Rini; Eprilurahman, Rury; Hakim, Lukman; Arisuryanti, Tuty; Rohmah, Zuliyati; Trijoko, Trijoko (Jurnal Biologi Udayana; Vol 25 No 1 (2021): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2021.v25.i01.p02, 2021)
Macrobrachium genus has many species members and distributed in various countries including Indonesia. One of the species belonging to the Macrobarachium genus that can be found in Indonesia was Macrobrachium sintangense or known as Sunda River Prawn. Identification of this species is important as an effort to expand studies on Sunda River Prawn in the Region of Yogyakarta. Identification of this species was carried out morphologically and molecularly with the 16S gene. The purpose of this study was to determine the morphological and molecular characters of M. sintangense . Morphological identification is done by identifying morphological, morphometric, and meristic characters according to the identification key. Molecular analysis was carried out by isolation, amplification, electrophoresis, and DNA visualization with UV illuminators, DNA sequencing by 1st Base. The results of this study indicate the morphological character of the rostrum slightly curved upwards or like a knife, rounded post antennular carapace, absent preanal carina, pubescene in the proximal half to two thirds of the chela. Morphologically, all samples were identified as members of the genus Macrobrachium . There are eight (8) specimens identifiable to the species level, as M. sintangense . The results of molecular identification of two (2) specimens showed a high similarity value and a close relationship with M. sintangense from GenBank samples and also close relationship with M. sintangense from Tukad Panti, Bali, Indonesia. The conclusion of this research is that morphologically and molecularly, the samples found in the Winongo.